Joint Power and Channel Allocation for Underlay D2D Communications with Proportional Fairness - Liu, Miaomiao; Zhang, Li; You, You (International Wireless Communications and Mobile Computing Conference (Online), 2019)
Since D2D (Device-to-Device) communication was proposed in cellular network as a new paradigm for enhancing network performance, many works have been done on resource allocation to improve system throughput and energy efficiency (EE) for underlay D2D communications. However, the system long-term average fairness as one of the system main performance metrics was rarely considered especially when users are moving. In this paper, we formulate the joint power and channel allocation problem aiming at maximizing the system fairness subject to the minimum required SINRs (Signal to Interference and Noise Ratios) and power consumption limits of cellular and active D2D links. To solve the above problem practically, we first decompose our original problem into two sub-problems (power and channel allocation), then solve them sequentially. Simulation results show that our proposed algorithm can dramatically enhance the system fairness and slightly improve the system throughput comparing with existing method.